Representasi Maskulinitas Dalam Iklan Kahf “Kahf Face Wash #JalanYangKupilih” (Analisis Semiotika Roland Barthes) - Rizky Maharani, Hanny; Faikar Urfan, Noveri (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research discusses the representation of new masculinity in the Kahf Face Wash #JalanYangKupilih skincare product advertisement on the Kahfeveryday Youtube channel account. Advertising media often presents the reality of masculinity that has developed in society through its products. In the past, male models with masculine images would only be featured in advertisements with themes sports, automotive, and energy drinks, while the main focus of beauty and facial care products only used female models. However, with the change in the meaning of being reconstructed in the new masculinity identity (metrosexual), advertising producers began to involve men in advertising facial care products. The purpose of this research is to see the value of masculinity representation in Kahf advertisements with a qualitative descriptive approach. Signs seen in the phenomenon of masculinity are examined with denotative, connotative, and mythical meanings from Roland Barthes' semiotic theory. The data acquisition was then studied using the theory of masculinity traits explained by David and Brannon also John Beynon in his book. The research from the data findings show a change in the meaning of masculinity towards metrosexuality which can be seen from men who become consumers of facial care products as a lifestyle need.Kata kunci: Iklan, Maskulinitas Baru, Representasi, Semiotika Roland Barthes